(untitled) (Raparin Journal of Humanities (RJH), 2025)
Cartographic representation is essential for each field of geography science, but representation of elements of climate is more important; therefore, we cannot see some climate elements, but we can feel them. We can see and determine the spatial differences for all elements of the climate on the map and in the cartographical representation. Also, this study is important because cartography and maps are essential for illustrating climate conditions in the study area. To reach an accurate result in our research, we relied on the representation elements of climate in the study area, as well as the use of an analysis method and use (ArcGIS) for representation, and created maps in the Dukan district. In the end, we have reached some results; that is, some of them are: the best way to represent and create maps for elements of climate is to use equal lines, like drawing isobars, isotherms, isohyets, and colour hierarchy. In conclusion, we reach that there are significant differences between winter and summer months in all climate elements in the study region, but the differences between spring and autumn months are smaller and more moderate in all climate elements.